Prevalence of major INSTI and HIV-1 drug resistance mutations in pre- and antiretroviral-treated patients in Indonesia - Djojosugito, Fauzia A.; Arfianti, Arfianti; Wisaksana, Rudi; Siregar, Fajri M.; Nasronudin, Nasronudin; Rachman, Brian E.; Khairunisa, Siti Q.; Indrati, Agnes R. (Narra J, 2024)
Indonesia has one of the highest HIV infection rates in Southeast Asia. The use of dolutegravir, an integrase strand transfer inhibitor (INSTI), as a first-line treatment underscores the need for detailed data on INSTI drug resistance mutations (DRMs). Currently, there is a lack of comprehensive data on DRMs INSTI and other HIV drug resistance in Indonesian patients, both pre- and post-treatment. The aim of this study was to identify the subtypes and drug resistance mutations of the protease, reverse transcriptase, and integrase genes in both treatment-naive and ARV-treated patients in Bandung, West Java, Indonesia. A cross-sectional study was conducted involving HIV-positive patients at Hasan Sadikin Hospital, Bandung, Indonesia, from September 2022 to January 2023. The patients were categorized into two groups: ARV-treated and pre-treatment patients. Peripheral blood mononuclear cells (PBMCs) were processed for DNA extraction, followed by amplification and sequencing of the pol gene to detect mutations and subtypes. The study found that the predominant subtype was CRF01_AE, accounting for 85.4% and 69% of pre-treatment and treated patients, respectively, followed by recombinant forms such as A1/CRF01_AE, CRF01_AE/CRF02_AG, subtype B, and other subtypes. Among ARV-treated/INSTI-naive patients, major INSTI DRMs R263K and Y143H were identified, while pre-treatment patients exhibited accessory integrase DRMs. The most common DRMs detected were non-nucleoside reverse transcriptase inhibitor (NNRTI) DRMs, with prevalences of 14.6% and 7% in pre-treatment and ARV-treated patients, respectively. In conclusion, CRF01_AE emerged as the predominant subtype in both pre-treatment and ARV-treated patients in Bandung, underscoring the necessity for ongoing surveillance of integrase DRMs, particularly given the presence of major INSTI DRMs in patients undergoing INSTI treatment.